Survival and deterioration time of walking abilities in dogs homozygous for the SOD1 gene mutation with and without thoracolumbar intervertebral disc protrusion - Sebestyén, Péter; Kowalska, Malwina Ewa; Golini, Lorenzo (Frontiers in Veterinary Science, 2025)
IntroductionDogs homozygous for the SOD1 gene mutation with presumptive degenerative myelopathy (DM) can develop concurrent intervertebral disc protrusion (IVDP). The impact of IVDP on the progression of SOD1-related clinical signs is unknown. The aim of this study was to describe a population of dogs with the SOD1 mutation and to compare survival and time to non-ambulation between those with and without IVDP.MethodsThis single-center exploratory cohort study was preregistered and retrospectively included dogs with the SOD1 gene mutation, compatible clinical signs, and available spinal magnetic resonance imaging (MRI). Dogs were divided into two groups based on the presence (IVDP+) or absence (IVDP-) of IVDP affecting the T3-L3 spinal cord segment. The primary outcomes were time to euthanasia from the onset of clinical signs (neurological deficits) and from the diagnosis (genetic testing and MRI). The secondary outcome was time to non-ambulatory status. Data were analyzed using descriptive statistics and survival analysis.ResultsA total of 39 dogs were enrolled in the study, with a mean age of 115 months and a mean weight of 29 kg at the time of diagnosis. The most common breed was the German Shepherd (n = 9/39). In the IVDP- group (n = 28/39), the median survival time was 13 months (95% CI: 9–18 months) from the onset of clinical signs, and 6 months (95% CI: 5–11 months) from the time of diagnosis. In the IVDP+ group (n = 11/39), the median survival time was 11 months (95% CI: 9-∞ months) from the onset of clinical signs, and 7 months (95% CI: 5-∞ months) from the diagnosis. Cox regression analysis indicated that dogs with IVDP had a hazard ratio of 1.20 for euthanasia (95% CI: 0.58–2.49, p = 0.6), which was not statistically significant compared to dogs without IVDP.DiscussionBased on this retrospective cohort, dogs with the SOD1 mutation appear to have similar disease progression and survival, regardless of the presence of concurrent IVDP.Clinical trial registrationThe study has been preregistered on https://preclinicaltrials.eu/ (PCT ID: PCTE0000406).